ChemInform Abstract: A Rapid Entry to Amino Acid Derived Diverse 3, 4‐Dihydropyrazines and Dihydro[1, 2, 3]triazolo[1, 5‐a]pyrazines Through 1, 3‐Dipolar Cycloaddition. Issue 44 (4th November 2014) - Bera, Saurav; Panda, Gautam
Abstract A simple synthetic route to enantiomerically pure 5‐methyl‐3, 4‐dihydropyrazines (VIII), triazolo[1, 5‐a]pyrazines (II) and (IV) and triazolo[1, 5‐a][1, 4]diazocine (VI) starting from commercially available amino acids derived synthetic intermediates is described.